2018
DOI: 10.1016/j.jvs.2017.06.099
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of primary endovascular repair of the ascending aorta

Abstract: Despite the absence of a dedicated aortic stent graft for the ascending aorta, patients with a range of ascending aortic diseases are being successfully treated by endovascular technologies. For optimal outcomes, patient selection is critical to align aortic anatomy with the limited device sizing options, and it should be reserved for patients at high surgical risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 57 publications
0
100
0
Order By: Relevance
“…On the other hand, new invasive techniques in the ascending aorta, such as endovascular repair, have been developed, with promising results. 19 Although their main indication is currently reserved for patients with high surgical risk, as less invasive techniques they may potentially provide a future solution in some of these cases.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…On the other hand, new invasive techniques in the ascending aorta, such as endovascular repair, have been developed, with promising results. 19 Although their main indication is currently reserved for patients with high surgical risk, as less invasive techniques they may potentially provide a future solution in some of these cases.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…In most cases of ascending aortic stenting, the stent graft must be customised because of individual anatomical variations. A systematic review by Muetterties et al 20 revealed a significant variation in the stent graft choices among different endovascular approaches. Thirteen different aortic stent grafts were used in 118 patients, with the majority being thoracic aortic stent grafts (71.2%).…”
Section: Risk Stratificationmentioning
confidence: 99%
“…A recent systematic review from 1995 to 2017 reported that TEVAR for the ascending aorta was performed in 118 patients. 44 The aortic pathologies treated involved type A dissection (50%), pseudoaneurysm (30%), and others (20%), including penetrating ulcer, and true aneurysm. The overall survival rate was 15.2%, and ARD rate was 5%.…”
Section: Tevar For Ascending Arch Aneurysm and Type A Dissectionmentioning
confidence: 99%